“Wherever I could move around”: The worldmaking work of gays and girls in the archived photographs and testimony of Kewpie of District Six - Ramsden-Karelse, R (2022)
In 1998, the recently established Gay and Lesbian Archive of South Africa acquired 600 photographs and three interviews conducted with their original collector, Kewpie. The Kewpie Collection, as it is now known, remains the only official archival resource that depicts and was created by the collective of people from District Six, Cape Town, who described themselves as gays and girls and referred to each other using she/her pronouns after being assigned male at birth. Classified “Coloured” under apartheid, the girls were forcibly removed from District Six after it was declared “Whites Only” in 1966. Three decades later, as legal apartheid was being dismantled, the constitution of the Kewpie Collection as such was informed by a proliferation of historiographical and archival practices coupled with the urgent emergence of the question of gay rights within the public sphere. Notwithstanding its intentions and successes, one effect of the Collection’s archivalisation has been to obscure the fundamental work gays and girls undertook to both survive and imagine other ways of being in the world.